Determination of Plant Season Based on Oldeman Agri Climate Zone and Utilization of Regulation Food Crops Cropping Patterns in Kisar Island, Southwest Maluku Regency - Laimeheriwa, Semuel; Madubun, Elia Leonard; Risamasu, Robby Gerald; Luhukay, Marcus (Universitas Pattimura, 2025)
Oldeman agroclimate zone is a classification system used to group areas based on rainfall distribution patterns and soil moisture potential available throughout the year. This system provides a clearer picture of which areas are suitable for certain crops based on their water needs, as well as optimizing the use of existing climate resources through cropping patterns arrangements. This study aims to identify and analyze Oldeman agroclimate zones to determine the right planting season and develop efficient food crop cropping patterns on Kisar Island. This study combines two approaches, namely descriptive and quantitative with the following analysis stages: generating rainfall data, calculating average regional rainfall, determining agroclimate zones, determining planting seasons, and arranging cropping patterns. The results of the study indicate that Kisar Island is included in Agroclimate Zone E3 with a planting season length of 7 months, starting in December and ending in June. Intercropping or mixed cropping patterns are options in corn and legume cultivation. To avoid water shortages during the reproductive phase of the plant, dryland rice planting should be carried out in the period from March to June.